Impact of kinematic modification in the underwater undulatory swimming performance of a swimmer - Audot, D. A. G.; Hudson, D. A.; Warner, M.; Banks, J. (ISBS Proceedings Archive (Michigan), 2023)
This work is a case study observing the impact of various kinematics modifications in the simulated pressure forces and hydrodynamic work done by an athlete performing maximum effort Underwater Undulatory Swimming (UUS). The studied athlete was recorded using a Motion Capture methodology. Seven key joints were identified to represent the athlete`s motion and their position were fitted with a fourth order Fourier series. This kinematic data was then modified to reduce or amplify the upper-body and lower-body motion but also to have a linear wave propagation. The kinematics (10 in total) were inputted in an unsteady 2D Computational Fluid Dynamics (CFD) solver, Lily Pad. Results suggest directions for improvement in the execution of the athlete`s swimming style, whether it is for reducing the hydrodynamic work done or minimising resistive forces.